Co-production in the public Sector Experiences and Challenges - Mariagrazia Fugini, Enrico Bracci (Springer, 2016)
This book examines the various ways in which co-production can contribute to the creation, design, and delivery of public services, namely by engaging the expertise of users and their networks, by promoting public services that are better targeted and more responsive to users, by cutting costs against the background of austerity in public finance, by creating a synergy between government and civil society that will impact positively on social capital, and by addressing the challenges resulting from growing democratic and citizenship deficits. Particular attention is paid to local government and the health and social care sector. After definition of the concept of co-production, the critical issues which arise when public services are co-produced are discussed. Various experiences of co-production are presented and analyzed with a view to highlighting why, how, and with what effect public service co-production may be implemented. Individual chapters focus on the impact of co-production in making cities smarter and the use of ICT in supporting co-production of public services. The book will be of relevance to a wide readership, from students to academics and professionals interested or engaged in public service management